Analisis Yuridis Pembatalan Akta Wasiat yang Melibatkan Harta Bersama: Studi Putusan Mahkamah Agung Nomor 1983 K/Pdt/2017 - Hastarini, Arvita (Zaaken: Journal of Civil and Business Law, 2026)
Death as a legal event causes consequences in the form of the transfer of the property of the heir to the heir through the inheritance mechanism stipulated in the Civil Code and the compilation of Islamic law. One of the forms of inheritance is the will as stipulated in Article 875 of the Civil Code, which, in principle, is a unilateral legal act and can be made in the form of an authentic deed by a notary in order to guarantee legal certainty. However, the freedom of Will is not absolute, especially when the object of the Will is the common property of the marriage, which, according to the law of marriage, requires the consent of both parties. This study uses normative juridical method with statute approach, based on primary, secondary, and tertiary legal materials that are analyzed descriptively. A review of the Supreme Court Decision No. 1983 K/Pdt / 2017 shows that the Supreme Court affirms that the freedom of testamentair is limited by the provisions regarding joint property as lex specialis, so that the transfer without the consent of the spouse is declared legally defective and null and void. The implication is that although the Will has perfect evidentiary power outwardly, formally, and materially, the power remains subject to the fulfillment of material conditions and must not conflict with the law. This ruling emphasizes the balance between legal certainty, justice, and the protection of the rights of spouses and heirs in the Indonesian legal system.